Gaseous neuromodulators in the control of neuroendocrine stress axis. - Navarra, P; Dello Russo, C; Mancuso, C; Preziosi, P; Grossman, A (2000)
The gaseous neuromodulator carbon monoxide has been shown to reduce the stimulated release of stress neuropeptides, such as vasopressin and oxytocin, from the rat hypothalamus in vitro, while evidence concerning corticotropin-releasing hormone is controversial. In vivo studies have been conducted in the rat, inhibiting heme oxygenase activity--and hence carbon monoxide biosynthesis--in the central nervous system by means of specific heme oxygenase blockers; these studies showed that basal heme oxygenase activity tends to oppose exaggerated increases in vasopressin secretion following immune-inflammatory challenges, whereas it favors the normal rise in circulating ACTH which follows footshock. Another gas normally produced in mammalian brains under basal conditions, hydrogen sulfide, also appears to play a role in the control of the hypothalamo-pituitary-adrenal axis. Indeed, increases in hydrogen sulfide levels within the hypothalamus, either obtained with hydrogen sulfide-enriched media or by the addition of the hydrogen sulfide precursor S-adenosyl-methionine, are associated with the inhibition of the stimulated release of corticotropin-releasing hormone from rat hypothalamic explants. Parellel in vivo experiments in the rat under resting conditions and after stress-induced adrenocortical activation show that S-adenosyl-methionine significantly reduces the rise in serum corticosterone levels caused by 1-h exposure to cold. These results demonstrate the pathophysiological importance of both carbon monoxide and hydrogen sulfide in the regulation of neuroendocrine function.